Neurons in Dorsal Anterior Cingulate Cortex Signal Postdecisional Variables in a Foraging Task - Blanchard, Tommy C. (Society for Neuroscience, 2014)
The dorsal anterior cingulate cortex (dACC) is a key hub of the brain's executive control system. Although a great deal is known about its role in outcome monitoring and behavioral adjustment, whether and how it contributes to the decision process remain unclear. Some theories suggest that dACC neurons track decision variables (e.g., option values) that feed into choice processes and is thus “predecisional.” Other theories suggest that dACC activity patterns differ qualitatively depending on the choice that is made and is thus “postdecisional.” To compare these hypotheses, we examined responses of 124 dACC neurons in a simple foraging task in which monkeys accepted or rejected offers of delayed rewards. In this task, options that vary in benefit (reward size) and cost (delay) appear for 1 s; accepting the option provides the cued reward after the cued delay. To get at dACC neurons' contributions to decisions, we focused on responses around the time of choice, several seconds before the reward and the end of the trial. We found that dACC neurons signal the foregone value of the rejected option, a postdecisional variable. Neurons also signal the profitability (that is, the relative value) of the offer, but even these signals are qualitatively different on accept and reject decisions, meaning that they are also postdecisional. These results suggest that dACC can be placed late in the decision process and also support models that give it a regulatory role in decision, rather than serving as a site of comparison.